A Secure Fusion: Elliptic Curve Encryption Integrated with LSB Steganography for Hidden Communication - El-Taj, Homam (International Journal of Computational and Experimental Science and Engineering, 2024)
In today's digital age, ensuring secure communication is essential. This article presents a novel approach for hidden communication by integrating Elliptic Curve Encryption (ECE) with Least Significant Bit (LSB) Steganography. Our proposed fusion offers a robust solution, Stegno Curve for concealing sensitive information within innocuous cover media while encrypting it using elliptic curve cryptography. By leveraging the strengths of both techniques, we achieve enhanced security and confidentiality in data transmission. Through a comprehensive literature review, methodology explanation, security analysis, and implementation details, we demonstrate the feasibility and effectiveness of the Stegno Curve Method. The findings of this study not only contribute to advancing the field of secure communication but also open avenues for practical applications in various domains, such as secure cloud transitions, smart home technologies, and data encryption.